Meio eletrônico: uma das formas de diminuição do tempo de duração do processo no 4º Juizado Especial Cível de Porto Velho/RO - Baldan, Guilherme Ribeiro (2011)
The State exerts the jurisdictional function aiming at the litigious conflict composition, being the process the way in which it gets materialized. With this, the access to justice is considered as a guarantee of a pretension examination, in acceptable time, with the security of an adjusted treatment, which is a reflection of society values. The Judiciary Power suffers critics of all sorts: nowadays in Brazil, the delaying is the mostly pointed problem. So much that Brazilian society started to demand a solution for this with such a great emphasis, that the reasonable duration of the process was enclosed in the roll of the Constitution of the Republic individual guarantees. Many alternatives have been searched intending to reduce the process duration time, the electronic way being one of these options. In the year of 2006, Law 11,419 came into use, it deals with the action at law computerization. This study it carried through an evaluation of the context that led to the search for a fast litigations solution, with the analysis of the law which instituted the electronic media in the process transaction, restricted to this optics of the process duration time reduction. On the basis of a case study carried through in 4º Civil Special Court at the Porto Velho Judicial district, It has been demonstrated that, at least in this jurisdictional unit, there was an effective reduction in the process duration time. The Action at law - PJe was pondered, still, concerning the free software that is available for the National Justice Council for use by the courts, electronic, concluding that the tool will serve as an instrument for the reduction of the process final term. This dissertation was finished with considerations on the issues studied, standing out the idea of that all the actors involved in conflicts solution must contribute so that the peace be reached.